Children’s rights system in the Republic of Latvia in compliance with international law regarding out-of-family care system - Madara, Siliņa (Riga Graduate School of Law, 2020)
Children rights have been defined in international and domestic legal systems. Despite the ongoing development of children’s rights, it is still a relatively new legal subset of human rights. So far, under the United Nation Convention on the Rights of the Child, there has been the establishment of international and regional legal acts concerning the rights of the child. As a party to different international and regional legal acts, the Republic of Latvia has to undertake obligations to respect and ensure children’s rights in its jurisdiction. However, the necessity to examine international law before domestic legal acts of the Republic of Latvia is to allege full comprehension of a sense of responsibility regarding children’s rights. Two hypotheses of the Republic of Latvia children’s rights system is developed and analysed. However, first, this research examines and conceptualises the characteristics of children’s rights and conducts a legal analysis of international law. Legal acts are characterized by their level/hierarchy, the sophistication of autonomy, and functions those provide. Eventually, the legal analysis does not find conflict between legal norms or legal acts. Although the children rights are regulated in various legal acts and different legal systems, the hypotheses have not been approved. Nevertheless, the analysis of children rights in out-of-family care raises some inconsistencies.
Keywords: Children rights; Latvia